Albert Ballin (English edition) - Gerhardt, Johannes (Mäzene für Wissenschaft, 2010)
His was an unprecedented rise to the top: from the thirteenth child of a poor Jewish emigrant agent to the "sovereign of shipping" and "friend" of the Kaiser. It is hardly surprising that Alfred Ballin was one of the foremost figures of Wilhelmine Empire. From the beginning, he attracted attention at Hamburg-Amerikanische Packetfahrt-Aktien-Gesellschaft, known as Hapag for short. Under its manager Ballin, Hapag became the largest shipping line in the world.From 1907 until his tragic death on November 9th 1918, Ballin belonged to the board of trustees of the Hamburg Scientific Fondation, to which he also contributed in a special way.Ballin's biography sketches the unusual life of this man, who personified perhaps more than any of his comtemporaries the prominence and power of the second German Empire but at the same time also experienced its limits and weaknesses.